Resistance Plasmids of Pseudomonas aeruginosa: Change from Conjugative to Nonconjugative in a Hospital Population - Korfhagen, Thomas R. (1976)
Properties of a population of carbenicillin- and gentamicin-resistant, tobramycin-susceptible Pseudomonas aeruginosa at Veteran's Administration Hospital, Cincinnati, Ohio, have been followed during a 16-month period. As originally described, the strains were isolated from patients with urinary tract colonizations and were predominantly Parke-Davis immunotype 7. For the majority of these organisms, antibiotic resistance was correlated with the presence of a self-conjugative plasmid of incompatibility group P-2. The source and relative incidence of multiply resistant isolates have remained constant during the current study, but the immunotype has shifted form type 7 to type 2. Concomitantly, the population has lost the property of conjugative transfer of resistance, and resistant strains are now compatible with P-2 plasmids. A group P-2 R plasmid, pMG5, will mobilize resistance markers, demonstrating that the multiple resistance of the nonconjugative strains is mediated by R plasmids. Additionally, gentamicin resistance due to either conjugative or nonconjugative plasmids is correlated with the presence of similar gentamicin acetyltransferase activity. pMG5-mobilized plasmids are shown to be incompatible with pMG5. pMG5 is also shown to mobilize resistance markers from nontransferring antibiotic-resistant strains representing populations from Parkland Memorial Hospital, Dallas, Texas, and Cleveland Clinic Foundation, Cleveland, Ohio.